Pneumotoraks dan pneumomediastinum sebagai komplikasi trakeostomi darurat - Arie Cahyono (PERHATI-KL, 2010)
Background: Tracheostomy is a surgical procedure making an opening into the trachea to provide anairway passage. It can cause complications such as subcutaneous emphysema, pneumothorax andpneumomediastinum. Purpose: To remind ENT specialists and general practitioners about the risk ofpneumothorax and pneumomediastinum in tracheostomy procedure and its management. Case: Wereported one case of 62 years old man who had grade 3 airway obstruction and had to be tracheostomizedand got subcutaneous emphysema, pneumothorax and pneumomediastinum as complications. Case management: Water sealed drainage (WSD) was inserted and he also underwent chest physiotherapy.Conclusion: Tracheostomy which was done in emergency can increase the risk of pneumothorax andpneumomedistinum complications, and could be avoided if the patient had come sooner. The insertion ofWSD combined with chest physiotherapy were the treatment of choice for patient with massive pneumothraxand pneumomediastinum after tracheostomy.Key words : tracheostomy, emphysema, pneumothorax, pneumomediastinum. Abstrak : Latar belakang: Trakeostomi adalah tindakan bedah membuat lubang di trakea untuk membebaskan jalan napas. Tindakan ini dapat menyebabkan komplikasi berupa emfisema subkutis, pneumotoraks danpneumomediastinum. Risiko komplikasi meningkat pada trakeostomi darurat. Tujuan: Kasus ini diajukanuntuk membahas pneumotoraks dan pneumomediastinum sebagai komplikasi trakeostomi sehingga dokterumum dan dokter spesialis THT dapat meningkatkan kewaspadaannya. Kasus: Dilaporkan satu kasuslaki-laki 62 tahun yang menderita sumbatan jalan napas grade 3 sehingga perlu tindakan trakeostomidarurat Pasca tindakan terjadi emfisema subkutis disertai pneumotoraks luas dan pneumomediastinum.Penatalaksanaan: Dilakukan pemasangan water sealed drainage (WSD) dan dikombinasikan denganfisioterapi dada. Kesimpulan: Trakeostomi yang dilakukan darurat dapat meningkatkan risiko tejadinyapneumotoraks dan pneumomediastinum, yang dapat dihindari jika pasien lebih cepat didiagnosis.Pemasangan WSDdengan fisioterapi dada merupakan terapi pilihan pada pasien pneumotoraks luas danpneumomediastinum pasca trakeostomi. Kata kunci: trakeostomi, emfisema, pneumotoraks,pneumomediastinum.